1981
DOI: 10.1083/jcb.90.1.176
|View full text |Cite
|
Sign up to set email alerts
|

Pit formation and rapid changes in surface morphology of sympathetic neurons in response to nerve growth factor.

Abstract: Scanning and transmission electron microscope studies were carried out on the rapid cell surface responses of cultured newborn rat sympathetic neurons to nerve growth factor (NGF), a substance that promotes their survival and differentiation. The somas of sympathetic neurons continuously exposed to NGF or deprived of the factor for 4-5 h have a very smooth surface. After readdition of NGF to the latter type of cultures, there is rapidly initiated a transient, sequential change in the cell surface. Microvilli a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…In the same experiments we noted that NGF treatment markedly increased clathrinimmunostained puncta at or near the plasma membrane . Although consistent with earlier, as well as more recent, observations on the effect of NGF, EGF, and insulin (Connolly et al, 1981(Connolly et al, , 1984Corvera, 1990;Wilde et al, 1999), the extent of the change and its rapidity were impressive. Quite unexpectedly, we also found that most (ϳ80%) clathrin puncta near the surface of NGF-treated cells failed to stain for TrkA, suggesting that clathrin was recruited to membranes containing little or no TrkA.…”
Section: Abstract: Ngf; Bdnf; Neurotrophin; Signaling; Trka; Clathrisupporting
confidence: 75%
See 1 more Smart Citation
“…In the same experiments we noted that NGF treatment markedly increased clathrinimmunostained puncta at or near the plasma membrane . Although consistent with earlier, as well as more recent, observations on the effect of NGF, EGF, and insulin (Connolly et al, 1981(Connolly et al, , 1984Corvera, 1990;Wilde et al, 1999), the extent of the change and its rapidity were impressive. Quite unexpectedly, we also found that most (ϳ80%) clathrin puncta near the surface of NGF-treated cells failed to stain for TrkA, suggesting that clathrin was recruited to membranes containing little or no TrkA.…”
Section: Abstract: Ngf; Bdnf; Neurotrophin; Signaling; Trka; Clathrisupporting
confidence: 75%
“…How the interaction of these components is regulated is of considerable interest. It has been known for some time that polypeptide growth factor signals influence the formation of coated membranes (Connolly et al, 1981(Connolly et al, , 1984. Greene and colleagues showed in PC12 cells treated with NGF that the number of clathrin-coated plasma membrane densities increased two-to threefold within 30 sec of NGF addition (Connolly et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-induced clathrin-redistribution to the plasma membrane has been previously reported for epidermal growth factor (EGF) and nerve growth factor (NGF) 43 . There, the binding of EGF to its receptor causes phosphorylation of the clathrin heavy chain and a global redistribution of clathrin to the cell periphery to form CCPs 44 .…”
Section: Discussionmentioning
confidence: 99%
“…While ligand-induced clathrin-redistribution to the plasma membrane has been previously reported for epidermal growth factor (EGF) and nerve growth factor (NGF) [41], these cases involve global changes in the distribution of clathrin in the cell. The binding of EGF to its receptor causes phosphorylation of the clathrin heavy chain and a global redistribution of clathrin to the cell periphery [42].…”
Section: Dynamics Of Influenza Endocytosismentioning
confidence: 99%